Water calorimetry-based kQ factors for Farmer-type ionization chambers in the SOBP of a carbon-ion beam - Holm, Kim Marina; Jäkel, Oliver; Krauss, Achim (Physics in medicine and biology, 2021)
The dosimetry of carbon-ion beams based on calibrated ionization chambers (ICs) still shows a significantly higher uncertainty compared to high-energy photon beams, a fact influenced mainly by the uncertainty of the correction factor for the beam quality kQ. Due to a lack of experimental data, kQ factors in carbon-ion beams used today are based on theoretical calculations whose standard uncertainty is three times higher than that of photon beams. To reduce their uncertainty, in this work, kQ factors for two ICs were determined experimentally by means of water calorimetry for the spread-out Bragg peak of a carbon-ion beam, these factors are presented here for the first time. To this end, the absorbed dose to water in the C-12-SOBP is measured using the water calorimeter developed at Physikalisch-Technische Bundesanstalt, allowing a direct calibration of the ICs used (PTW 30013 and IBA FC65G) and thereby an experimental determination of the chamber-specific kQ factors. Based on a detailed characterization of the irradiation field, correction factors for several effects that influence calorimetric and ionometric measurements were determined. Their contribution to an overall uncertainty budget of the final kQ factors was determined, leading to a standard uncertainty for kQ of 0.69%, which means a reduction by a factor of three compared to the theoretically calculated values. The experimentally determined values were expressed in accordance with TRS-398 and DIN 6801-1 and compared to the values given there. A maximum deviation of 2.3% was found between the experiment and the literature.
Im Titel und in der Beschreibung ist bei der Zeichenfolge kQ das Q tiefgestellt
Gesehen am 09.09.2021